2023
DOI: 10.3390/w15132423
|View full text |Cite
|
Sign up to set email alerts
|

Design of Cost-Effective and Sustainable Treatments of Old Landslides Adapted to the Moroccan Road Network: A Case Study of Regional Road R410 Crossing the Rifan Structural Domain

Omar Inabi,
Mustapha Attou,
Mostafa Benzaazoua
et al.

Abstract: The Moroccan road network is susceptible to multiple landslides annually, particularly in the northern regions due to high rainfall and specific geology. These events result in significant economic and social negative consequences, highlighting the need for sustainable and cost-effective solutions for network maintenance. This study outlines the methodology employed in addressing the issues within the RR410 regional road (Rifain region of Morocco), which entailed a thorough examination of the malfunctions, spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…However, their implementation in anthropic materials has posed a challenge for this project, given the heterogeneity of the PMWR piles and the difficulty of carrying out mechanical characterizations that accurately reflect the actual behavior of the deposited materials. [18] have shown that an infrastructure built on a natural slope of only 15 • can lead to major instability issues. Therefore, conducting a specialized study that considers both the soil's characteristics at the location and the intended construction is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…However, their implementation in anthropic materials has posed a challenge for this project, given the heterogeneity of the PMWR piles and the difficulty of carrying out mechanical characterizations that accurately reflect the actual behavior of the deposited materials. [18] have shown that an infrastructure built on a natural slope of only 15 • can lead to major instability issues. Therefore, conducting a specialized study that considers both the soil's characteristics at the location and the intended construction is crucial.…”
Section: Introductionmentioning
confidence: 99%